PENGARUH BRAND AMBASSADOR DAN DIGITAL MARKETING TERHADAP PURCHASE INTENTION PRODUK Y.O.U - Indriyani, Happy Riska; Tobing, Rudy (Lembaga Pengembangan Kinerja Dosen, 2023)
The cosmetics industry is currently a very large business prospect and provides a fairly broad market opportunity. One of the marketing strategies used by beauty companies is the use of brand ambassadors and digital marketing to compete, maintain and increase the company's profit level. This study aims to determine the effect of Brand Ambassador and Digital Marketing on Purchase Intention of Y.O.U Products. The sample in this study were 78 respondents. The method of determining the sample in this study using simple random sampling. The data analysis method used is the Multiple Linear Regression method using the SPSS 23 program. The results of this study indicate that Brand Ambassador has a positive and significant effect on Purchase intention, and Digital Marketing also has a positive and significant effect on Purchase intention. In addition, Brand Ambassador and Digital marketing have a simultaneous effect on Purchase Intention.